Main limitations and effects of Alzheimer's in the elderly population: A narrative review (Research, Society and Development, 2023)
Faced with the assiduous growth of the elderly population in the world, notably in developing countries, substantially and without having an effective social structure to meet this demand, there is a proportional increase in cases of chronic degenerative pathologies, which brings with them numerous challenges and questions, in view of the social daily life of the elderly and notably in their family context. In this bias, it denotes that Alzheimer's disease is one of the main challenges, both for the caregiver and for the carrier, due to it being a chronic neurodegenerative disease, and that in contemporary times its causes are unknown, it is incurable and causes several disorders to the carrier and the people in your midst. According to the Brazilian Alzheimer's Association (Abraz) the number of elderly people who suffer from this disease has been growing exorbitantly, and through the various obstacles brought with it, it is observed that the care provided is of great importance, both for the elderly and their families. In this bias, it is crucial to understand the main limitations and effects that Alzheimer's imposes on elderly patients. In the current work, it will be approached through a bibliographic review, regarding the main limitations and effects that Alzheimer's imposes on the elderly patient. The objective of this study was to analyze the main limitations and effects that Alzheimer's imposes on elderly patients, addressing the numerous obstacles that the pathology brings with it, in addition to understanding how computerization can be advantageous in the care of elderly patients with Alzheimer's.